Infrastructures of a market economy - Bezvercha, A. I.; Pererva, P. G. (My University, 2023)
Infrastructure acts as a mechanism for the functioning of entrepreneurship. It fills a huge economic space from production to consumption. Accepting manufactured products, organizes the conclusion of supply contracts, promotes the development of commodity flows in industries and regions, regulates sales and maintenance of the economic system.
Keywords: market economy; infrastructure; insurance; banks; production; enterprise